Generic assumptions in utterance interpretation: the case of indirect instructions - Aitken, Martin (HERMES - Journal of Language and Communication in Business, 2002)
This article addresses the role played by genre in the way in which language users interpret ‘indirect’ directive utterances in the special discourse context of technical instructions. In linguistics, issues of genre have most often been approached from socially oriented frameworks such as systemic functional linguistics and the ethnomethodology of the Swales-Bhatia school. The present article instead adopts the cognitive framework of relevance theory to account for a process of comprehension founded on two modularised cognitive processes, viz. decoding of semantic content and relevance-driven inferential manipulation of resulting representations to which generic assumptions about the discourse provide significant contextual input.